El papel de la Universidad pública en la construcción de indicadores para estudios socioeconómicos - Quiñónez-Cabeza, Betty Maribel; Preciado-Ramírez, Joffre Danny; Preciado-Ortiz, Félix Lenin (Editorial Grupo AEA, 2026)
This study analyzes the role of public universities in the construction of socioeconomic indicators and their impact on regional development. A qualitative approach is employed to classify universities based on their capacity to generate reliable data and collaborate in public policy formulation. Through a comprehensive literature review and analysis of university examples from Latin America, Europe, Asia, and Africa, the study highlights how educational institutions influence the creation of key indicators such as the Human Development Index (HDI), poverty rates, and the Gini Index. The findings show that the most influential public universities tend to have strong connections with international organizations, allowing them to access resources and improve the validity of these indicators. This research contributes to the field of socioeconomic development by providing a replicable methodology to evaluate the impact of universities on the use of indicators for policy design. The conclusions emphasize the importance of strengthening collaboration between universities and governments to improve the quality and accuracy of studies that guide public policy decisions.